ЗАСОБИ КОМПЛЕКСНОГО ПРОЕКТУВАННЯ ДЛЯ ВДОСКОНАЛЕННЯ ЕЛЕКТРОМЕХАНІЧНИХ СИСТЕМ З АСИНХРОННИМИ ДВИГУНАМИ - Попович, O.M.; Головань, І.В. (Інститут електродинаміки НАН України, Київ, 2022)
The stages, methodology and complex design tools of electromechanical systems with inductions motors are substantiated. A quantitative assessment of the possibilities of increasing their economic efficiency using complex design according to the criterion of maximum income is provided. The expressions of complex criteria of efficiency, complex mathematical models and research methods are substantiated. The change in economic efficiency is determined when the value of design parameters deviates from the optimal value. Using the developed means of complex design can increase economic efficiency by tens of percent is shown. References 22, table 1, figures 2.